(untitled) (Jurnal Teknologi (Sciences & Engineering), 2014)
To capture the seakeeping performance of a catamaran with asymmetric demi-hulls, tank tests were carried out in regular head waves using a scaled model with 2.036 m in length. The lateral space between the demi-hulls was changed in the tests as W/B=2.55, 2.90 and 3.25, where W denotes breadth overall and B the breadth of the demi-hull. Also, two models with different water lines of inside flat and outside round (IF-type) and of outside flat and inside round (OF-type) were used. OF-type is superior to IF-type in both ship motion and added resistance performances in waves at the design speed. In IF-type series, the smallest clearance, W/B=2.55 is the best in the added resistance performance.